HUBUNGAN POLA ASUH ORANG TUA DENGAN TINGKAT KECEMASAN ANAK PADA ADAPTASI SEKOLAH DI SEKOLAH DASAR NEGERI CILANDAK BARAT 04 PAGI JAKARTA SELATAN - Duma Lumban Tobing (Indonesian Journal of Health Development, 2019)
Inability to adapt to the new environment at the beginning of the school children can cause anxiety response. This study aims to determine the relationship between parenting parents to a child's anxiety levels during elementary school adaptation with total sample 54 respondents . The sample was parents who have children who were new students at SDN 04 Morning Cilandak Barat, South Jakarta in the academic year 2013-2014. This study used a descriptive quantitative method with a " cross sectional ". Analysis of the data used were univariate and bivariate analysis using Chi Square test. The results showed that the greatest frequency of parents' parenting is authoritative / democratic as many as 28 people (51.9 %), the largest frequency of a child's anxiety level was mild anxiety as many as 30 people (55.6 %). Bivariate analysis results about parenting parents relationship with the child's anxiety levels during school adaptation obtained p value (0.007) was smaller than the value of alpha (0.05), so it can be concluded that the presence of a significant relationship between the two variables, which means Ha received that there was a relationship between parenting parents with children on the anxiety level adaptation period school. And based on this analysis that good parenting can affect a child's anxiety reduction. For educational institutions SDN 04 Morning Cilandak Barat, South Jakarta necessary meetings between parents and teachers to discuss parenting parents that can be applied at home and provide information to parents about good parenting and for further research should examine significantly and a more specific description of the characteristics of parenting and anxiety level and the factors that affect the level of anxiety